Training strategies to maintain immunocompetence in athletes - Pyne, D. B.; Gleeson, M.; McDonald, W. A.; Clancy, R. L.; Perry, C.; Fricker, P. A. (International Journal of Sports Medicine, 2000)
Clinical experience and empirical evidence have led to the modeling of exercise and training as a form of stress on the immune system. Coaches, athletes, and medical personnel are seeking guidelines on ways to reduce the risk of illness that compromises training or competitive performance. The immune system is influenced by a wide range of physical, environmental, psychological, and behavioural factors which, combined with clinical assessment, collectively form the basis of the following intervention strategies: 1) training: careful management of training volume and intensity, variety to overcome training monotony and strain, a periodised approach to increasing loads, and provision of adequate rest and recovery periods; 2) environmental: limiting initial exposure when training or competing in adverse environmental conditions (heat, humidity, altitude, air pollution) and acclimatising where appropriate; 3) psychological: teaching athletes self-management and coping skills and monitoring of athletes' responses to the psychological and psychosocial stresses of high-level training and competition; 4) behavioural: adopting a well-balanced diet with adequate intake of macro- and micro-nutrients, limiting transmission of contagious illnesses by reducing exposure to common infections, airborne pathogens, and physical contact with infected individuals; and 5) clinical considerations: medical screening, pathology testing, immunization and prophylaxis, and routine management of illness-prone athletes. Future experimental studies are required to develop and enhance the effectiveness of these strategies in reducing illness in athletes.